Indeks Ekologi dan Kepadatan Komunitas Cerithidea Spp. di Perairan Pengudang dan Dompak - Aulia Permata Pohan; Ayie Davila Lubis; Bagus Feri Sumantri; Fikri Ardani; Gerri Syahrial; Juliana Juliana; Noor Ai`in; Nuri Khoiriah; Mikhael Rajustinus Ginting; Muhamad Reda; Santika Della Risdianti Putri; Siti Mardiana (Populer: Jurnal Penelitian Mahasiswa, 2024)
Macrozoobenthos is a group of benthic organisms measuring more than 1 mm that plays a crucial role in the process of decomposition and mineralization of organic material in aquatic ecosystems. The purpose of this observation was to determine the ecological index and density of macrozoobenthos in Pengudang and Dompak Waters. This observation was conducted from May 26-27, 2024 in the waters of Pengudang and Dompak using the survey method. Determination of sampling points is done by random sampling of 20 points each line transect. Macrozoobenthos measurements using 1x1m quadrant transect. The results showed that Pengudang waters had a higher species density with an average value of 13 (medium) compared to Dompak with an average of 0.03 (low). The diversity index ranged from 0.36-1.05, with Pengudang showing higher values. The uniformity index in Pengudang was 0.50 (medium), and in Dompak 0.17 (low). The dominance index was higher in Dompak (0.84) than Pengudang (0.40). Water quality parameters showed that temperature, salinity and pH were within safe limits, but TSS values in Dompak exceeded quality standards, indicating higher sedimentation levels.